PKM STUDY OF CLASSICAL TEXTS AS A MEANS OF STRENGTHENING ISLAMIC KNOWLEDGE AT SULTAN HASANUDDIN ISLAMIC BOARDING SCHOOL IN LIMBUNG GOWA - Fauziah Bachtiar; Muhammad Radhi Almardhi; Muhammad Yasin; Tauhidah Bachtiar (PT. Jurnal Center Indonesia Publisher, 2025)
Classical texts, or 'Kitab Kuning', are one of the main sources of Islamic knowledge after the Qur'an and Hadith. Islamic boarding schools (Pesantren) are educational institutions that consistently preserve the study of classical texts for their students. The purpose of this study is to provide training and understanding to the students, especially prospective alumni, about the importance of classical texts as a means to strengthen Islamic knowledge, which will serve as a foundation for engaging with society. The results of the program implementation show that this training has a significant impact on the students in understanding the importance of classical texts as a primary source of Islamic education, particularly in addressing various religious issues commonly encountered in society. It also helps students realize that the study of classical texts is not outdated or boring, but rather enjoyable and enriching in expanding their Islamic knowledge